Prevalensi, Karakteristik, dan Faktor Risiko Penderita Peripartum Cardiomyopathy di RS.Hasan Sadikin Bandung - Hawani Sasmaya Prameswari; Augustine Purnomowati; Toni M Aprami (The Indonesian Heart Association, 2015)
Background. Peripartum cardiomyopathy (PPCM) is one of the important health problem and can be fatal. The aim of this study is to determine the prevalence and characteristics of patients with PPCM in the Hasan Sadikin Hospital (RSHS).Methods. Data were retrieved retrospectively from medical records at the Cardiology and Vascular Medicine, RSHS, Bandung, from 1stJanuary2011 to 31thDecember, 2013. The analysis was performed using SPSS 21 and Chi Square significance test.Results.Eighty (26.23%,) subjects with PPCM out of 305 women with pregnancy or postpartum and cardiovascular complications are paticipated. The PPCMproportion are significantly decrease by time from 51.25%, 27.5%, 21,25% in 2011, 2012, and 2013 respectively. The average age was 30.3±7.9years. Deliveries were cesarean delivery in 43.8%, pervaginal in 37.5%, forceps in 15%, and vacuum-extractor in 3.8%. Preeclampsia was found in 43.8% of patients and most of them with NYHA functional class IV (86.3The average ejection fraction of 34.8±7.5%.Conclusion. The prevalence of PPCM in RSHS is 26.23%, with the majority (86.3%) was NYHA functional class IV.Significant risk factorsof PPCM were age over 30 years, multiparous, low socioeconomic, and preeclampsia.